Preparation method of single crystal lithium alloy negative electrode and metal lithium battery
Through stacking and pressurization, the negative electrode of single crystal lithium alloy is prepared, which solves the problems of lithium dendrites growth and volume changes, simplifies the preparation process, improves the stability and performance of the battery, and extends the cycle life.
Patent Information
- Application Number
- CN202411654524.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The lithium metal negative electrode of existing metal lithium batteries is prone to lithium dendrites growth and volume changes during charging and discharging, which greatly reduces the cycle stability. Moreover, the preparation method of lithium alloy negative electrode is complex and costly, making it difficult to control the alloy composition and structure, affecting the battery. performance.
By stacking single crystal lithium foil with lithium-philic metal foil and pressurizing it, orderly diffusion of single crystal lithium atoms and lithium-philic metal atoms is achieved, thickness ratio and pressure are regulated, single crystal lithium alloy foil is prepared, and the preparation process is simplified. Expand the types of alloys and improve electrochemical properties.
It significantly improves the electrochemical performance and stability of the battery, reduces the preparation cost, achieves uniform lithium deposition, and extends the cycle life of the battery.
Smart Images

Figure CN119230761A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a technology in the field of lithium batteries, specifically a method for preparing a single crystal lithium alloy negative electrode and a metal lithium battery. Background Art
[0002] The existing lithium metal negative electrode of metal lithium batteries is prone to lithium dendrite growth and large volume changes during the charge and discharge process, which not only reduces the cycle stability of the battery, but also may cause safety hazards. Lithium alloy negative electrode materials have attracted much attention due to their good stability and safety. However, the existing lithium alloy negative electrode preparation methods often have problems such as complex processes, high costs, and difficulty in controlling alloy composition and structure, which limits their wide application in metal lithium batteries. At the same time, the regulation of the diffusion dynamics of lithium atoms in negative electrode materials is also the key to improving the performance of metal lithium batteries. Current technology still has deficiencies in improving the diffusion dynamics of lithium atoms on the electrode surface and in the bulk phase, making it difficult to achieve uniform lithium deposition, thereby affecting the cycle stability of the battery. Single crystal alloy negative electrodes with low diffusion barrier crystal planes show excellent performance, but their preparation methods are relatively cumbersome and limited to alloy materials. Summary of the invention
[0003] In view of the shortcomings of the prior art, which have complicated steps and a single pressurization form, the present invention proposes a method for preparing a single-crystal lithium alloy negative electrode and a metal lithium battery, which can simplify the preparation process, increase the types of single-crystal lithium alloys, and significantly improve the electrochemical performance and stability of the battery, fully demonstrating its outstanding effectiveness in improving battery performance.
[0004] The present invention is achieved through the following technical solutions:
[0005] The invention relates to a method for preparing a single crystal lithium alloy negative electrode. The method comprises the following steps: a single crystal lithium foil and a lithium-philic metal foil are stacked and then pressurized to achieve mutual diffusion of ordered single crystal lithium atoms and lithium-philic metal atoms. The thickness ratio and pressure of the single crystal lithium foil and the lithium-philic metal foil are adjusted to control the atomic diffusion process so as to achieve ordering and alloying of atomic arrangement. A single crystal alloy lithium foil is prepared and a single crystal metal negative electrode is obtained after cutting.
[0006] The lithium-philic metal is selected from materials suitable for alloying with lithium metal to form lithium alloys, which include but are not limited to: indium, magnesium, zinc, aluminum or tin.
[0007] The stacking means that the single crystal lithium foil and the lithium-philic metal foil are stacked in a form of overlapping areas to achieve uniform diffusion of atoms during the pressurization process.
[0008] Preferably, the surface areas of the single crystal lithium metal foil and the lithium-philic metal foil are the same.
[0009] The ratio of the thickness of the single crystal lithium metal foil to the thickness of the lithium-philic metal foil is 0.1-50.
[0010] The pressurization is preferably static pressurization, rolling pressurization, or reciprocating pressurization perpendicular to the surfaces of the single crystal lithium foil and the lithium-philic metal foil.
[0011] The pressurization is preferably carried out at a temperature of 20°C to 180°C.
[0012] The pressure range is: 50-600MPa.
[0013] The invention relates to the application of the single crystal lithium alloy foil prepared by the method, which is used for preparing the negative electrode of a metal lithium battery using an electrolyte or a solid electrolyte after cutting.
[0014] The positive electrode of the metal lithium battery is made of, but not limited to, oxide positive electrode materials, polyanion positive electrode materials, sulfur positive electrode materials, etc.
[0015] The electrolyte is realized by any of the following methods:
[0016] ①1M LiPF6 dissolved in a mixed solution of EC:DEC=1:1Vo l%,
[0017] ②10.2M LiPF6, 0.2M LiBF4, 0.8M LiDFOB dissolved in a mixed solution of DEC:FEC=2:1Vol%,
[0018] ③ 1M LiTFSI was dissolved in a mixed solution of DME:DOL=1:1 Vol%.
[0019] The solid electrolyte adopts Li7La3Zr2O 12 Solid electrolyte, Li6PS5X (X = Cl, Br, I) solid electrolyte, Li 10 GeP2S 12 Solid electrolyte, Li7P3S 11 Solid electrolyte, Li3InCl6 solid electrolyte or Li3YCl6 solid electrolyte. Technical Effects
[0020] The present invention directly realizes the preparation of a single crystal lithium alloy negative electrode by applying pressure at a certain temperature, and by adjusting the temperature and the pressurization process, the mutual diffusion of single crystal lithium atoms and lithium-philic metal atoms is regulated to achieve the ordering and alloying of atomic arrangement, wherein the pressurization process can adopt a variety of pressurization methods, which is suitable for different alloying materials and expands the types of single crystal lithium alloys. Compared with the prior art, the present invention reduces the synthesis steps and the preparation cost, and the prepared single crystal lithium alloy significantly improves the lithium ion lithium transport kinetics on the electrode surface and in the bulk phase, promoting uniform lithium deposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a schematic diagram of the process of preparing a single crystal lithium metal foil in Example 1 of the present invention;
[0022] Figure 2 is a physical picture of the single crystal lithium alloy foil prepared in Example 1 of the present invention;
[0023] Figure 3 1 is an XRD diagram of the single crystal lithium alloy negative electrode prepared in Example 1 of the present invention and Comparative Example 1;
[0024] Figure 4 The present invention conducts cycle performance tests and comparisons on the single crystal lithium alloy negative electrode prepared in Example 1 and the lithium alloy negative electrode prepared in Comparative Example 1, respectively, by assembling batteries with LPSCl solid electrolyte at a rate of 5C. DETAILED DESCRIPTION Example 1
[0025] like Figure 1 As shown, this embodiment relates to a method for preparing a single crystal lithium alloy negative electrode, comprising:
[0026] S1: prepare a single crystal lithium foil with a certain thickness A1 and a lithium-philic indium foil with a certain thickness A2; A1 / A2=10;
[0027] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, and applying a pressure of 150 MPa by vertical static pressure at room temperature (25° C.) to prepare a single crystal lithium alloy foil;
[0028] S3: Cutting the single crystal lithium alloy foil into single crystal lithium alloy negative electrodes with a diameter of 10 mm;
[0029] The prepared single crystal lithium alloy anode was assembled into a battery with NCM811 as the oxide cathode and Li6PS5Cl solid electrolyte.
[0030] like Figure 2 As shown in FIG. 1 , a physical picture of the single crystal lithium alloy prepared in this embodiment is shown in FIG. Figure 3 As shown in the XRD diagram on the left, the lithium alloy foil prepared in this embodiment is a single crystal. Figure 4 As shown in the left figure, the assembled battery was cycled under 5C conditions, and the battery capacity did not decay after 100 cycles. Example 2
[0031] This embodiment relates to a method for preparing a single crystal lithium alloy negative electrode, comprising:
[0032] S1: prepare a single crystal lithium foil with a certain thickness A1, and prepare a lithium-philic indium foil with a certain thickness A2; A1 / A2=5;
[0033] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, applying a pressure of 100 MPa by roller pressing at room temperature (25° C.), to prepare a single crystal lithium alloy foil;
[0034] S3: Cut the single crystal lithium alloy foil into single crystal lithium alloy negative electrodes with a diameter of 10 mm.
[0035] The prepared single crystal lithium alloy negative electrode was assembled into a battery with LFP as a polyanion positive electrode, 0.2M LiPF6, 0.2M LiBF4, and 0.8M LiDFOB dissolved in an electrolyte with DEC:FEC=2:1Vol%.
[0036] The lithium alloy foil prepared in this embodiment is a single crystal lithium indium alloy with a thickness of 150 microns. The assembled battery is subjected to a cycle test under 1C conditions. The capacity retention rate of the battery after 100 cycles is 97%. Example 3
[0037] This embodiment relates to a method for preparing a single crystal lithium alloy negative electrode, comprising:
[0038] S1: prepare a single crystal lithium foil with a certain thickness A1, and prepare a lithium-philic indium foil with a certain thickness A2; A1 / A2=2.
[0039] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, applying a pressure of 200 MPa by roller pressing at room temperature (25° C.), to prepare a single crystal lithium alloy foil;
[0040] S3: Cut the single crystal lithium alloy foil into single crystal lithium alloy negative electrodes with a diameter of 10 mm.
[0041] The prepared single crystal lithium alloy negative electrode is assembled into a battery with a sulfur positive electrode and a Li6PS5Cl solid electrolyte.
[0042] The lithium alloy foil prepared in this embodiment is a single crystal lithium indium alloy with a thickness of 50 microns. The assembled battery is subjected to a cycle test under 0.3C conditions. The capacity retention rate of the battery after 100 cycles is 92%. Example 4
[0043] This embodiment relates to a method for preparing a single crystal lithium alloy negative electrode, comprising:
[0044] S1: prepare a single crystal lithium foil with a certain thickness A1, and prepare a lithium-philic zinc foil with a certain thickness A2; A1 / A2=15;
[0045] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, and applying a pressure of 400 MPa by vertical static pressure at 50° C. to prepare a single crystal lithium alloy foil;
[0046] S3: Cut the single crystal lithium alloy foil into single crystal lithium alloy negative electrodes with a diameter of 10 mm.
[0047] The prepared single crystal lithium alloy negative electrode was mixed with NCM811 and Li7La3Zr2O as the oxide positive electrode. 12 Solid electrolyte assembled batteries.
[0048] The lithium alloy foil prepared in this embodiment is a single crystal lithium zinc alloy with a thickness of 150 micrometers. The capacity retention rate of the battery after 100 cycles at 1C is 99%. Example 5
[0049] This embodiment relates to a method for preparing a single crystal lithium alloy negative electrode, comprising:
[0050] S1: prepare a single crystal lithium foil with a certain thickness A1, and prepare a lithium-philic aluminum foil with a certain thickness A2; A1 / A2=20;
[0051] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, applying a pressure of 500 MPa by roller pressing at 60° C. to prepare a single crystal lithium alloy foil;
[0052] S3: Cut the single crystal lithium alloy foil into single crystal lithium alloy negative electrodes with a diameter of 10 mm.
[0053] The prepared single crystal lithium alloy negative electrode was assembled into a battery with NCM811 and Li6PS5Cl solid electrolyte as the oxide positive electrode.
[0054] The lithium alloy foil prepared in this embodiment is a single crystal lithium aluminum alloy with a thickness of 100 micrometers. The capacity retention rate of the battery after 100 cycles at 3C is 99%. Example 6
[0055] This embodiment relates to a method for preparing a single crystal lithium alloy negative electrode, comprising:
[0056] S1: prepare a single crystal lithium foil with a certain thickness A1, and prepare a lithium-philic magnesium foil with a certain thickness A2; A1 / A2=20;
[0057] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, and applying a pressure of 500 MPa at 120° C. by vertical static pressing to prepare a single crystal lithium alloy foil;
[0058] S3: Cut the single crystal lithium alloy foil into single crystal alloy negative electrodes with a diameter of 10 mm.
[0059] The prepared single crystal lithium alloy negative electrode was assembled into a battery with NCM811 and Li6PS5Cl solid electrolyte as the oxide positive electrode.
[0060] The lithium alloy foil prepared in this embodiment is a single crystal lithium-magnesium alloy with a thickness of 180 micrometers. The capacity retention rate of the battery after 100 cycles at 0.5C is 98%. Example 7
[0061] This embodiment relates to a method for preparing a single crystal lithium alloy negative electrode, comprising:
[0062] S1: prepare a single crystal lithium foil with a certain thickness A1, and prepare a lithium-philic tin foil with a certain thickness A2; A1 / A2=30;
[0063] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, and applying a pressure of 450 MPa by vertical static pressing at 150° C. to prepare a single crystal lithium alloy foil;
[0064] S3: Cut the single crystal lithium alloy foil into single crystal alloy negative electrodes with a diameter of 10 mm.
[0065] The prepared single crystal lithium alloy negative electrode was assembled into a battery with NCM811 and Li6PS5Cl solid electrolyte as the oxide positive electrode.
[0066] The lithium alloy foil prepared in this embodiment is a single crystal lithium-magnesium alloy with a thickness of 120 micrometers. The capacity retention rate of the battery after 100 cycles at 1C is 99%. Comparative Example 1
[0067] This comparative example relates to a method for preparing a lithium alloy negative electrode, comprising:
[0068] S1: prepare a polycrystalline lithium foil of a certain thickness A1, and prepare a lithium-philic indium foil of a certain thickness A2; A1 / A2=10;
[0069] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, and applying a pressure of 150 MPa by vertical static pressure at room temperature (25° C.) to prepare a lithium alloy foil;
[0070] S3: Cut the lithium alloy foil into lithium alloy negative electrodes with a diameter of 10 mm.
[0071] The prepared lithium alloy negative electrode was assembled into a battery with NCM811 and Li6PS5Cl solid electrolyte as the oxide positive electrode.
[0072] like Figure 3 As shown in the figure on the right, the lithium alloy foil prepared in this comparative example is polycrystalline and has a thickness of 100 microns. Figure 4 As shown in the figure on the right, the capacity of the battery begins to decay rapidly after 60 cycles at 5C. Comparative Example 2
[0073] This comparative example relates to a method for preparing a lithium alloy negative electrode, comprising:
[0074] S1: prepare a polycrystalline lithium foil of a certain thickness A1, and prepare a lithium-philic indium foil of a certain thickness A2; A1 / A2=10;
[0075] S2: overlapping the single crystal lithium foil and the lithium-philic metal foil, and rolling them at room temperature (25° C.), and rolling them 3 times in a reciprocating unidirectional manner under a pressure of 100 MPa to prepare a lithium alloy foil;
[0076] S3: Cut the lithium alloy foil into lithium alloy negative electrodes with a diameter of 10 mm.
[0077] The prepared lithium alloy negative electrode and LFP as a polyanion positive electrode, 0.2M LiPF6, 0.2M LiBF4, and 0.8MLiDFOB were dissolved in an electrolyte with DEC:FEC=2:1Vol% to assemble a battery.
[0078] The lithium alloy foil prepared in this comparative example is polycrystalline and has a thickness of 50 microns. The capacity retention rate of the battery after 100 cycles at 1C is 90%. Comparative Example 3
[0079] S1: In a glove box filled with argon, a lithium-magnesium alloy with a thickness of 200 μm and a lithium content of 27 wt.% was placed in a roller press.
[0080] S2: Set the roller press temperature to 100°C.
[0081] S3: The lithium-magnesium alloy in step S1 is rolled forward three times until the deformation amount reaches 80%.
[0082] S4: placing the lithium-magnesium alloy in step S3 in a muffle furnace and performing aging treatment at 100° C. for 1 hour.
[0083] S5: Cool naturally to room temperature to prepare a single crystal lithium-magnesium alloy.
[0084] The prepared single crystal lithium alloy negative electrode was assembled into a battery with NCM811 and Li6PS5Cl solid electrolyte as the oxide positive electrode.
[0085] The lithium alloy foil prepared in this embodiment is a single crystal lithium-magnesium alloy, and the capacity retention rate of the battery after 100 cycles at 0.5C is 95%.
[0086] XRD characterization was performed on the single crystal lithium alloy negative electrode prepared in Example 1 and the lithium alloy negative electrode prepared in Comparative Example 1. Figure 3 As shown, the XRD patterns of the metallic lithium alloys prepared by the steps of Example 1 and Comparative Example 1 show that the lithium alloy foil prepared in Example 1 is single crystal, and the lithium alloy foil prepared in Comparative Example 1 is polycrystalline.
[0087] The single crystal lithium alloy negative electrode prepared in Example 1 and the lithium alloy negative electrode prepared in Comparative Example 1 were respectively compared with LPSCl solid electrolyte assembled batteries at a rate of 5C. Figure 2 As shown, the capacity of the battery assembled with the single crystal lithium alloy negative electrode prepared in Example 1 has not decayed after 100 cycles, and the capacity of the battery assembled with the lithium alloy negative electrode prepared in Comparative Example 1 begins to decay rapidly after 60 cycles, which indicates that the single crystal lithium alloy negative electrode exhibits better stability and the assembled battery also exhibits better electrochemical performance.
[0088] The single crystal lithium-magnesium alloy negative electrode prepared in Example 6 and the single crystal lithium-magnesium alloy negative electrode prepared in Comparative Example 3 were compared with LPSCl solid electrolyte assembled batteries at a rate of 0.5C. The capacity retention rate of the single crystal lithium-magnesium alloy prepared by the present method is higher than that of the single crystal lithium-magnesium alloy prepared by the method provided in Comparative Example 3.
[0089] Compared with the prior art, this method is simple and easy to operate, and is not limited to the type of alloy. The single-crystal lithium alloy prepared by direct single pressurization of this method has more outstanding capacity and better cycle stability than the polycrystalline lithium alloy and single-crystal lithium alloy prepared by the prior art.
[0090] The above-mentioned specific implementation can be partially adjusted in different ways by those skilled in the art without departing from the principle and purpose of the present invention. The protection scope of the present invention shall be based on the claims and shall not be limited by the above-mentioned specific implementation. Each implementation scheme within its scope shall be subject to the constraints of the present invention.
Claims
1. A method for preparing a single crystal lithium alloy negative electrode, characterized in that: By stacking a single crystal lithium foil and a lithium-philic metal foil and then pressurizing them, the ordered single crystal lithium atoms and the lithium-philic metal atoms can diffuse into each other. By adjusting the thickness ratio and pressure of the single crystal lithium foil and the lithium-philic metal foil, the atomic diffusion process is controlled to achieve ordering and alloying of atomic arrangement, and a single crystal alloy lithium foil is prepared. After cutting, a single crystal metal negative electrode is obtained.
2. The method for preparing a single crystal lithium alloy negative electrode according to claim 1, characterized in that: The lithium-philic metal is indium, magnesium, zinc, aluminum or tin.
3. The method for preparing a single crystal lithium alloy negative electrode according to claim 1, characterized in that: The stacking means that the single crystal lithium foil and the lithium-philic metal foil are stacked in a form of overlapping areas to achieve uniform diffusion of atoms during the pressurization process.
4. The method for preparing a single crystal lithium alloy negative electrode according to claim 1, characterized in that: The surface areas of the single crystal lithium metal foil and the lithium-philic metal foil are the same.
5. The method for preparing a single crystal lithium alloy negative electrode according to claim 1, characterized in that: The ratio of the thickness of the single crystal lithium metal foil to the thickness of the lithium-philic metal foil is 0.1-50.
6. The method for preparing a single crystal lithium alloy negative electrode according to claim 1, characterized in that: The pressurization includes static pressurization, rolling pressurization and reciprocating pressurization perpendicular to the surfaces of the single crystal lithium foil and the lithium-philic metal foil.
7. The method for preparing a single crystal lithium alloy negative electrode according to claim 1, characterized in that: The pressurization temperature is 20°C to 180°C.
8. The method for preparing a single crystal lithium alloy negative electrode according to claim 1, characterized in that: The pressure range is: 50-600MPa.
9. An application of a single crystal lithium alloy foil prepared by the method according to any one of claims 1 to 8, characterized in that: After cutting, it is used to prepare the negative electrode of metal lithium battery.
10. The use according to claim 9, characterized in that: The metal lithium battery adopts electrolyte or solid electrolyte, wherein: The electrolyte is realized by any of the following methods: ①1M LiPF6 dissolved in a mixed solution of EC:DEC=1:1Vol%, ②10.2M LiPF6, 0.2M LiBF4, 0.8M LiDFOB dissolved in a mixed solution of DEC:FEC=2:1Vol%, ③ 1M LiTFSI was dissolved in a mixed solution of DME:DOL=1:1Vol%; The solid electrolyte is Li7La3Zr2O 12 Solid electrolyte, Li6PS5X (X = Cl, Br, I) solid electrolyte, Li 10 GeP2S 12 Solid electrolyte, Li7P3S 11 Solid electrolyte, Li3InCl6 solid electrolyte or Li3YCl6 solid electrolyte.
Citation Information
Patent Citations
Lithium-indium alloy negative electrode material for lithium battery and preparation method thereof
CN113948693A
Single crystal lithium magnesium alloy, preparation method thereof and lithium metal battery
CN118880466A
Negative electrode for lithium secondary battery, lithium secondary battery using the negative electrode, and manufacture of the negative electrode for the lithium secondary battery
JP1999135116A
Lithium secondary battery
WO2022210443A1
